Laboratory confirmed shigellosis in Malagasy children - Rahajamanana, Lalaina V.; Andrianjakasolo, Paulin; Andriatahiana, Dera S.; Ravaoarisaina, Zakasoa; Raboba, Liliane J.; Rasamindrakotroka, Andry (International Journal of Research in Medical Sciences, 2022)
Background: Diarrheal diseases are a major public health problem in developing countries with high mortality and morbidity rates, especially among children. Shigella species is the leading cause of paediatric bacterial diarrhea and shigellosis data are very scarce in Madagascar. Methods: A 3 year retrospective study from January 2018 to December 2020, at the University Hospital Mother and Child Tsaralalàna laboratory was performed to assess the bacteriological and epidemiological characteristics of laboratory confirmed shigellosis cases. Results: During the study period, 298 stool samples were examined, of which 48 (16.1%) were positive for Shigella sp. The mean age of infected children was 29.7 months, predominantly in the 24-59 months age group. The infection was found mainly in male children (56.2%). Most isolates of Shigella sp showed resistance to co-trimoxazole and amoxicillin. All the strains were susceptible to third-generation cephalosporins. Of the isolated Shigella sp, 14 strains were tested for species identification and serotyping, twelve of which were Shigella flexneri and two were Shigella sonnei. The most frequent serotypes were S. flexneri 1b and 2a. Conclusions: This study found a Shigella sp positivity rate of 16.1%. This pathogen frequently infects infants age group. Bacteriology laboratory surveillance and a multicenter survey are essential to control the spread of drug-resistant Shigella and to monitor circulating strains and the burden of this disease. Awareness of water, hygiene and sanitation (WASH) and community water supply is also necessary to reduce this infection.